The Influence of Emotional Intelligence, Psychological Capital, and Work Engagement on Lateness Attitude and Turnover Intention of Life Insurance Employees in West Java - Rorefah Achmad Novrandy; Justine Tanuwijaya; Norzanah Mat Nor (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2026)
This study aims to analyze the influence of emotional intelligence, psychological capital, and work engagement on lateness-attitude and turnover intention among life insurance employees in West Java. This research focuses on identifying factors that contribute to employee lateness attitude and turnover intention in the life insurance industry. The data used in this study are primary data collected through an online questionnaire distributed via Google Forms to employees working in life insurance companies in West Java. Using a purposive sampling method, a total of 340 employees participated as respondents in this study. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The results indicate that emotional intelligence has a significant effect on work engagement but does not significantly influence psychological capital. Psychological capital is found to have a significant effect on work engagement. Furthermore, work engagement significantly affects both lateness attitude and turnover intention. The mediation analysis shows that psychological capital does not mediate the relationship between emotional intelligence and work engagement, while work engagement mediates the effect of psychological capital on lateness attitude. The findings suggest that companies should strengthen employee engagement initiatives and develop training programs that enhance emotional intelligence and psychological capital. These strategies can help organizations reduce employee lateness and turnover intention, thereby improving overall organizational performance.